2015
DOI: 10.1001/jamaoncol.2015.2510
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Mortality After a Diagnosis of Ductal Carcinoma In Situ

Abstract: Important risk factors for death from breast cancer following a DCIS diagnosis include age at diagnosis and black ethnicity. The risk of death increases after a diagnosis of an ipsilateral second primary invasive breast cancer, but prevention of these recurrences by radiotherapy does not diminish breast cancer mortality at 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
447
5
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(483 citation statements)
references
References 30 publications
16
447
5
15
Order By: Relevance
“…There are many papers that distinguish prognosis or analysis of DCIS, an early cancer without invasion, from invasive ductal carcinoma (IDC) (3,15,16). In this study, we also analyzed the cases that were upgraded to DCIS and IDC.…”
Section: Discussionmentioning
confidence: 99%
“…There are many papers that distinguish prognosis or analysis of DCIS, an early cancer without invasion, from invasive ductal carcinoma (IDC) (3,15,16). In this study, we also analyzed the cases that were upgraded to DCIS and IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Strong arguments for the treatment of DCIS in the same way as early invasive cancer are also presented in the publications in which the analysis of the data from the SEER register concerning 108 196 women with a diagnosis of DCIS confirms the fact that the clinical course of the disease in both groups of patients is similar [27,28]. One of the most essential contra-arguments against the reduction of local treatment, even in the group defined as low risk DCIS, is the lack of results of such randomised clinical studies as LORIS in Great Britain, which is a prospective study comparing surgical treatment (plus adjuvant radiotherapy or hormonotherapy) with an active observation, which was supposed to foster better understanding of the natural history of untreated DCIS [29].…”
mentioning
confidence: 84%
“…The basic arguments for the treatment of ductal carcinoma in situ in the same way as early invasive cancer comprise: -unknown natural history of untreated DCIS [16]; -high risk of undervaluation of the invasive component in the core-needle biopsy [10,[16][17][18]; -increase of recurrence risk with the progress of time [3,[19][20][21]; -lack of verified separators of the groups with the risk of adverse course of the disease [1,2,20]; -the results of the clinical studies confirming the justification of combined local treatment [22][23][24][25][26]; -and the proof that the clinical course of DCIS is the same as early invasive breast cancer [27,28]; -the lack of clinical studies which could justify a limitation of the treatment scope [28][29][30]. Given the fact that a large share of ductal carcinoma in situ is diagnosed as a small lesion seen only in a mammography image, and then treated with a mammotomy biopsy, a substantial part of DCIS is resected during this procedure.…”
mentioning
confidence: 99%
“…The group has urged that in situ diseases be called idles (indolent lesions of epithelial origin). However, a recent report from Narod et al 5 based on 108,196 registry cases of ductal carcinoma in situ might well modify that view. Narod reported that age greater than 35 years, black race, a large tumour, a high-grade tumour, or a tumour with comedonecrosis are all associated with a significantly greater risk of breast cancer death.…”
Section: Overdiagnosismentioning
confidence: 99%